Molecular formula analysis of fragment ions by isotope‐selective collision‐induced dissociation tandem mass spectrometry of pharmacologically active compounds. (December 2014) - Bianco, Giuliana; Buchicchio, Alessandro; Lelario, Filomena; Cataldi, Tommaso R.I.
<x xml:space="preserve">Abstract</x> The purpose of this work is to explore the mass fragment characterization of commonly used drugs through a novel approach, which involves isotope‐selective tandem mass spectrometry (MS/MS). Collision‐induced dissociation (CID) was performed with a low‐resolution linear ion trap mass spectrometer in positive electrospray ionization. Three pharmacologically active ingredients, i.e. omeprazole, meloxicam and brinzolamide, selected as model compounds in their own formulation, were investigated as a sodiated adduct [C17H19N3O3S + Na]+ (omeprazole) and as protonated adducts, [C14H13N3O4S2 + H]+ and [C12H21N3O5S3 + H]+, meloxicam and brinzolamide, respectively. Selecting a narrow window of ±0.5 m/z units, precursor ion fragmentation by CID‐MS/MS of isotopologues A + 0, A + 1 and A + 2 was found very useful to confirm the chemical formula of product ions, thus aiding the establishment of characteristic fragmentation pathways of all three examined compounds. The correctness of putative molecular formula of product ions was easily demonstrated by exploiting the isotope peak abundance ratios (i.e. IF+0/IF+1 and IF+0/IF+2) as simple constraints in low‐resolution MS instrumentations. Copyright © 2014 John Wiley & Sons, Ltd.